MANAGEMENT OF ENDOCRINE DISEASE: Pituitary tumour apoplexy. - Capatina, C; Inder, W; Karavitaki, N; Wass, J (2014)
Pituitary tumour apoplexy (PA) is a rare clinical syndrome that occurs as a result of acute haemorrhage and/or infarction within a frequently undiagnosed pituitary tumour. The sudden enlargement of the pituitary mass undergoing PA is responsible for a wide range of acute symptoms/signs (severe headache, visual loss, diplopia, hypopituitarism, impaired consciousness) which, together with the radiological evidence of a pituitary lesion, establish the diagnosis. The optimal care of PA requires involvement of a multidisciplinary team including endocrinologist, neurosurgeon, neuroophthalmologist and the management strategy depends on the clinical manifestations, as well as the presence of co-morbidities. Prompt surgical decompression is initially indicated in cases with severe or progressive impairment of the visual acuity or the visual fields or with altered mental state and leads to visual and neurological recovery in most of the patients. Patients with mild, stable clinical picture (including those with isolated ocular palsies) can be managed conservatively (support of fluid and electrolyte balance and stress doses of steroids in most cases) with favourable visual and neurological outcome. Frequent reassessment is mandatory because the clinical course can be unpredictable; if progression of symptoms occurs, later elective surgery is indicated and is beneficial, especially in terms of visual outcome. The endocrinological outcome is less favourable, irrespective of the treatment option, with many patients remaining on long-term replacement therapy. Despite the above guidelines, clear proof of optimal outcomes in the form of randomised controlled trials is lacking. Regrowth of the pituitary tumour years after a PA episode is possible and patients require long-term surveillance.